2015
DOI: 10.2138/am-2015-5161
|View full text |Cite
|
Sign up to set email alerts
|

Accurate determination of Fe3+/∑Fe of andesitic glass by Mössbauer spectroscopy

Abstract: To evaluate the accuracy of Fe 3+ and Fe 2+ ratios in silicate glasses determined by Mössbauer spectroscopy, we examine in detail the temperature (47-293 K) of Mössbauer spectra for two andesitic glasses, one quenched at 1 atm, 1400 °C (VF3) and the other at 3.5 GPa, 1600 °C (M544). Variabletemperature Mössbauer spectra of these two glasses are used to characterize the recoilless fraction, f, by two different methods-a relative method (RM) based on the temperature dependence of the ratios of Fe 3+ and Fe 2+ Mö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 61 publications
(89 reference statements)
3
20
0
1
Order By: Relevance
“…Dyar et al 434 (1987) also observed that wet chemical analyses yielded higher Fe 3+ , however, 435 their Fe 3+ contents were not directly from the fit of Mössbauer spectra. Similarly, 436 Jayasuriya et al (2004) showed that Fe 3+ /ΣFe in synthetic basaltic glasses 437 20 calculated from RT Mössbauer gave similar results to Fe 3+ /ΣFe calculated from 438Mössbauer spectra taken at 4.2 K, but both their RT and low temperature spectra 439 are complicated by strong non-paramagnetic components, which introduce 440 ambiguity to quantification of Fe 3+ /ΣFe(Zhang et al, 2015). Thus, there is no 441 consensus in the literature regarding whether Mössbauer and wet chemical 442 methods are consistent, or even in which direction the results may be biased.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Dyar et al 434 (1987) also observed that wet chemical analyses yielded higher Fe 3+ , however, 435 their Fe 3+ contents were not directly from the fit of Mössbauer spectra. Similarly, 436 Jayasuriya et al (2004) showed that Fe 3+ /ΣFe in synthetic basaltic glasses 437 20 calculated from RT Mössbauer gave similar results to Fe 3+ /ΣFe calculated from 438Mössbauer spectra taken at 4.2 K, but both their RT and low temperature spectra 439 are complicated by strong non-paramagnetic components, which introduce 440 ambiguity to quantification of Fe 3+ /ΣFe(Zhang et al, 2015). Thus, there is no 441 consensus in the literature regarding whether Mössbauer and wet chemical 442 methods are consistent, or even in which direction the results may be biased.…”
mentioning
confidence: 89%
“…The starting material of VF Series consists of a synthetic andesite similar in 92 5 composition to that used by O'Neill et al (2006) and Zhang et al (2015), and was 93 prepared from reagent oxides (SiO 2 , Al 2 O 3 , Fe 2 O 3 , TiO 2 , MgO), silicates 94 (CaSiO 3 ,Na 2 SiO 3 ) and stoichiometric sanidine glass. The Fe 2 O 3 consisted of 95 90% normal reagent oxide and 10% 57 Fe 2 O 3 (Isoflex, Inc) to obtain quality 96…”
Section: Starting Materials 91mentioning
confidence: 99%
See 3 more Smart Citations